Enhanced negative thermal expansion in MFI molecular sieves by varying framework composition - Bhange, Deu S.; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2010)
In the present investigations we have carried out the high temperature X-ray diffraction (HTXRD) studies on the metallosilicate molecular sieves iron silicalite-1 (FeS-1) samples of different Si/M ratios (Si/Fe = 50, 75, 100 and infinity) for their negative thermal expansion (NTE) behavior. All the samples exhibit NTE behavior in the temperature range 373-773 K. Systematic increase in negative thermal expansion coefficient is observed as a function of increasing Fe content in the MFI framework. Strength of the negative thermal expansion increases in the order Si/Fe = infinity < 100 < 75 < 50. It is concluded that by changing the composition of the framework of MFI, enhanced negative thermal expansion can be obtained. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: HTXRD; Negative thermal expansion; Silicalite-1